FRESH STATE PROPERTIES OF LIME MORTARS WITH FLAX OIL ADMIXTURE - Pavla Bauerová; Pavel Reiterman; Milena Pavlíková; Magdalena Kracík Štorkánová; Martin Keppert (Acta Polytechnica CTU Proceedings, 2019)
Flax oil has been used as mortar improving, hydrophobic, admixture already in ancient times. The paper describes the identification of flax oil in mosaic mortar from ca. 1900 by help of FTIR spectroscopy. This historic mortar was reproduced by nowadays raw materials and the influence of flax oil on consistency and air entraining of fresh mortar was tested. It was found that already small amount of oil caused significant air entrainment, which, simultaneously with water repellency action, may contribute to higher durability of mortar with oil admixture. The flux oil influenced also consistency of mortar; its presence caused higher flow value of mortar. Moreover, the introduction of the paper summarizes principal knowledge about action of natural admixtures in lime mortars and plasters on basis of current literature.